Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/17482631.2020.1744926
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and discrimination related to mental health and substance use issues in primary health care in Toronto, Canada: a qualitative study

Abstract: Purpose: Community Health Centres (CHCs) are an essential component of primary health care (PHC) in Canada. This article examines health providers' understandings and experiences regarding stigma towards mental health and substance use (MHSU) issues, as well as their ideas for an effective intervention to address stigma and discrimination, in three CHCs in Toronto, Ontario. Methods: Using a phenomenological approach, we conducted twenty-three interviews with senior staff members and peer workers, and three foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 44 publications
0
22
0
14
Order By: Relevance
“…Men with alcohol use disorder, which is considered masculine-typical, are perceived as more dangerous and are less tolerated than women with the disorder (Phelan & Basow, 2007). However, gender typicality is not always associated with greater stigma (e.g., Boysen & Logan, 2017; Murney et al, 2020).…”
Section: Gendermentioning
confidence: 99%
“…Men with alcohol use disorder, which is considered masculine-typical, are perceived as more dangerous and are less tolerated than women with the disorder (Phelan & Basow, 2007). However, gender typicality is not always associated with greater stigma (e.g., Boysen & Logan, 2017; Murney et al, 2020).…”
Section: Gendermentioning
confidence: 99%
“…However, as we did not find a strong correlation with other validation scales, this factor may represent a distinct environmental stressor related to perception instead of actual exposure and act more as a personal conversion factor that impacts mobility decisions (e.g., a chosen mode of transportation), for example, due to noise and traffic pollution and dissatisfaction related to relaxation (Marquart et al, 2021). Exclusion on the other hand was significantly but weakly related to Anxiety/Depression, Achievements, and Loneliness which was in the expected direction as discrimination have been found to affect mental health (Murney et al, 2020) as well as human capital (Caputo, 2002). In this situation, the domain Exclusion can act as a conversion factor whereas the domain Social support, which was related to the items Loneliness (HR-SWB), Attachment (ICECAP-A), and Anxiety/Depression (EQ-5D), included items such as "feeling supported if needed" and "ability to find people to engage with" which combines personal conversion factor and capabilities.…”
Section: Discussionmentioning
confidence: 94%
“… 13–15 Our recent research revealed that the levels of stigmatisation towards persons with MHSUP among health professionals within local community health centres (CHCs) were similar to those reported among other health workers in Canada. 16 17 Stigmatising attitudes and practices among health professionals are well documented throughout the literature, 18 and clients with MHSUP have reported stigmatising treatment from a variety of healthcare professionals 19 . One study found that stigmatisation may result in clients being threatened with coercive treatment, being provided with insufficient information, being regarded as lacking the capacity for responsible action or being patronised and/or humiliated.…”
Section: Introductionmentioning
confidence: 99%